Extrapulmonary small cell carcinoma of the breast. Case report - Torres-Cepeda, Duly (2022)
Small cell carcinoma accounts for 20% of lung cancers; it rarely occurs at other sites. Extrapulmonary small cell carcinoma is aggressive, with a propensity for regional and distant spread. This type of carcinoma is a rare breast neoplasm. Although the clinical appearance is nonspecific, it often responds well to therapy and has a good prognosis of survival. We present the case of a 50-year-old woman with extrapulmonary small cell carcinoma of the breast. Physical examination showed a 4 x 3 x 3 centimeters lesion confirmed by magnetic resonance imaging of the left breast. The diagnosis was made by biopsy showing characteristic small, round, lymphocyte-like cells with hyperchromatic nuclei and scant cytoplasm compatible with small cell carcinoma of the breast. The patient was treated with chemotherapy before undergoing total mastectomy and lymph node resection.